PENERAPAN PENGUKURAN NILAI WAJAR PSAK-KONVERGENSI IFRS DAN DAMPAKNYA PADA PILIHAN KEBIJAKAN AKUNTANSI DI INDONESIA - Siti Khomsatun (Jurnal Riset Akuntansi dan Keuangan, 2016)
Abstract. This study aims to investigate the impact of the compulsory measurement of fair value and choice on the comparability of financial statements. This study uses data from nonfinancial public companies listed on the BEI. The method of determining the appeal level using the Taplin index and the increase or decrease of the appeal rate using the different test of Mc Nemar and Wilcoxon. The results show that there is no increase in the comparability of financial statements for accounting policies required to use value measurement. The accounting policy allowed to choose the method of measurement is also not proven there is a decrease in the comparability of financial statements. Differences in appeals occur only in the accounting policies of fixed assets that have increased appeal. This study shows that before and after the adoption of new standards related to fair value measurement, the financial reporting appeal level is still high. This study also indicates that the fair value measurement for the accounting policy allowed to select the measurement method is still low.